The effect of Empowerment of Grandmother on Depression and Maternal Role Realization in Primiparae with Hospitalized Infant: A Randomized, Controlled, Clinical Trial - Somayyeh Tavasolnia; Maryam Ravanipour; Frahnaz Kamali; Niloofar Motamed; Shahnaz Pouladi (Journal of Evidence-Based Care, 2017)
Background:Hospitalization of the newborn infant can cause depression crisis and severely undermine the attainment and realization of maternal role in a primipara. The neonate’s maternal grandmother can provide the support needed to help the primipara avoid or overcome the ensuing problems. Aim: This study aimed to investigate the effect of empowerment of grandmothers on depression and maternal role realization in primiparae with hospitalized newborn. Method: In this randomized, controlled, clinical trial, 84 primiparae with their infants admitted to Shahid Rajaei Hospital of Gachsaran, Iran, were assigned to intervention and control groups. A grandmother empowerment intervention was devised by combining the concepts of Mercer’s theory with the stages of Ravanipour’s self-management empowerment model. The control group received the routine care. Depression and maternal role realization in all the primiparae were measured with Beck Depression Inventory and a researcher-made role realization questionnaire before and one month after the intervention. Data was analyzed by independent and paired t-test in SPSS, version 18. Results: The mean ages of the mothers in the intervention and control groups were respectively 27.02±5.3 and 24.0±4.1 years. Before the intervention, there was no significant difference between the depression scores (P>0.38) and role realization scores (P>0.40) of the subjects in the two groups; however, after the intervention, both scores showed significant differences (P